Signature Pedagogies and University Education: Towards Conscious Teaching - Ballardini, Helga; Serbati, Anna; Santucci Leoni, Anna (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
The concept of Signature Pedagogies raises a range of meaningful questions—firstly, at the linguistic level (such as how to effectively translate the expression into Italian), but even more so at the heuristic and pedagogical levels. What deep significance might this concept hold for educational research, particularly in teacher education—both for in-service and pre-service teachers—and in the students' learning process within university settings? This contribution stems from these reflections and aims to explore, through international literature and Italian research, possible ways to trans-ducere or transfer this concept, in order to outline a theoretical framework and practical proposals for the professional development of university teachers, especially within the broader context of Faculty Development. From this perspective, Signature Pedagogies are interpreted as keys to fostering pedagogical awareness and a professional stance grounded in the integrity of educational thinking and practice (Shulman, 2005) towards the development of teaching and learning processes and the quality of the academic system.